Hubungan Team Learning Capability (TLC) dan Supportive Work Environment (SWE) Pada Perguruan Tinggi Negeri dan Swasta di Indonesia - Aulia, Anisa; Maimunah, Siti; Komalasari, Shanty (Psikologi Prima, 2024)
This study aims to examine the relationship between Team Learning Capability (TLC) and a Supportive Work Environment (SWE) in public and private universities in Indonesia. The method used is a quantitative approach with data collected through questionnaires distributed online to 201 respondents, consisting of 98 public university students and 103 private university students. The correlation test results show a strong positive relationship between TLC and SWE in both types of universities, with Pearson's r values of 0.776 for public universities and 0.810 for private universities. The normality assumption test using the Shapiro-Wilk test indicates that the data is normally distributed. This study suggests that the higher the team learning capability, the more supportive the work environment in the universities. This conclusion underscores the importance of developing team learning capabilities to create a supportive work environment in the academic context.